2019
DOI: 10.1021/acsbiomaterials.9b01293
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Diffusion Printing: An Efficient Manufacturing Technique for Artificial Tubular Grafts

Abstract: Despite great progresses in bioprinting materials and technologies, immense challenges still remain when printing tubular tissues or organs with satisfying mechanical and chemical properties, such as blood vessel, colon, and trachea. Herein, a promising extrusion system based on an interfacial diffusion printing (IDP) technique for one-step printing of tubular tissue grafts is proposed. Specifically, this technique offers great convenience to prepare hollow hydrogel fibers with excellent mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Thus, an inner layer of calcium alginate when the sodium alginate solutions are extruded into a calcium chloride to produce the egg-box model hydrogel may be a viable, low-cost strategy. In addition, a method of sacrificial core materials can be used to construct a hollow core, calcium alginate hydrogel [15] , as acrylamide-calcium alginate hydrogels have been shown to possess excellent mechanical properties and biocompatibility [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an inner layer of calcium alginate when the sodium alginate solutions are extruded into a calcium chloride to produce the egg-box model hydrogel may be a viable, low-cost strategy. In addition, a method of sacrificial core materials can be used to construct a hollow core, calcium alginate hydrogel [15] , as acrylamide-calcium alginate hydrogels have been shown to possess excellent mechanical properties and biocompatibility [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5(c) illustrates the Schematic illustration of the inflammationmediated process for vascular remodeling and macroscopic observations of the vascular graft harvested after implantation for 1 month. Moreover, the ultrasonography clearly shows the blood flows normally at a speed of 39.4 cm/s in the grafted vascular 1 day after the implantation [236].…”
Section: Vascularmentioning
confidence: 91%
“…In a recent study, Zhou et al [236] introduced a convenient and efficient technique, designated as the interfacial diffusion for creating vascular tissue graft. In this method, hydrogel material was extruded into another medium and subjected to a diffusion gelation process.…”
Section: Vascularmentioning
confidence: 99%
“…The same authors also reported printing of a thermoresponsive alginate/poly(N-isopropylacrylamide) DN hydrogel using a similar procedure. 75 In one of the most thorough examples for applying the alginate/PAAm system in 3D printing, Zhou et al 76 printed tubes using interfacial diffusion printing (Figure 3). A bioink consisting of water, alginate, acrylamide, bacterial cellulose, MBAA, and ammonium persulfate (APS, initiator) is extruded into a reactive aqueous medium consisting of calcium chloride and tetramethylethylenediamine (TEMED, catalyst).…”
Section: Dn As Bioprintable Hydrogelsmentioning
confidence: 99%